Freshman Year Computer Engineering Students' Experiences For Flipped Physics Lab Class: An Action Research - GÜREL, ZEYNEP (AMER INST PHYSICS, 2017)
The purpose of this research is to determine the university students' learning experiences about flipped-physics laboratory class. The research has been completed during the fall semester of 2015 at Computer Engineering Department of Istanbul Commerce University. In this research, also known as a teacher qualitative research design, action research method is preferred to use. The participants are ten people, including seven freshman and three junior year students of Computer Engineering Department. The research data was collected at the end of the semester with the focus group interview which includes structured and open-ended questions. And data was evaluated with categorical content analysis. According to the results, students have some similar and different learning experiences to flipped education method for physics laboratory class.